Hubungan Kadar Hb-A1c (Glikosilasi Hemoglobin) dengan Komplikasi Makrovaskular pada Penderita Diabetes Melitus tipe 2 di RSUD Sanjiwani Gianyar - Anak Agung Gede Budhitresna; Suka Astini; I Gede Ari Purnama Putra (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Several studies have stated that HbA1c levels are known to be associated with the incidence of macrovascular complications in patients with type 2 diabetes. Patients often have higher HbA1c levels than non-diabetic patients, so it is used as a way to test blood sugar control for patients with type 2 diabetes. 2 to prevent complications. This study was done to assess the relationship between HbA1c levels and macrovascular complications so that HbA1c levels can be used to predict the prognosis and the main controller in preventing macrovascular complications. Analytic method was used and the design was cross-sectional. The research was done at the Sanjiwani Hospital Gianyar with a total sample of 53 people. The results of the chi-square test showed that t a significant relationship was found between Glycosylated Hemoglobin (HbA1c) levels and the incidence of macrovascular complications with p value = 0.021 with HbA1c levels as a risk factor with POR value = 1.705. The conclusion was that there was a significant relationship between HbA1c levels and the occurrence of macrovascular complications in patients with type 2 diabetes.